Pemodelan Proses Bisnis pada Dinas Pendidikan dan Kebudayaan Kota Balikpapan - Zakiah Zakiah; Lovinta Happy Atrinawati; Yuyun Tri Wiranti (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2021)
The Disdikbud of Balikpapan City has compiled 32 SOPs in 2017 and does not yet have documentation of ongoing business processes. The SOPs that have been prepared are still not fully in accordance with Permenpan RB Number 35 of 2012 and do not cover the entire process flow based on the main tasks and functions. This article presents a business process model using the principles of Business Process Modeling and Notation (BPMN) with the help of Bizagi Modeller software. Business Process Management (BPM) approach is used in modeling business processes to help improve business efficiency and effectiveness. From the results of the work, there are 69 business processes that have been modeled, divided into 55 processes in the Education Quality Improvement process and 14 processes in the Comfort, Security and Environmental Order Improvement process.Keywords: Education and Culture Office, Business Process, Standard Operating Procedure, Business Process Modeling and Notation, Business Process Management ABSTRAK. Disdikbud Kota Balikpapan telah menyusun 32 SOP pada tahun 2017 dan belum memiliki dokumentasi proses bisnis yang berjalan. SOP yang telah disusun masih belum sepenuhnya sesuai dengan Permenpan RB Nomor 35 Tahun 2012 dan belum mencakup keseluruhan alur proses berdasarkan tugas pokok dan fungsi. Artikel ini menyajikan model proses bisnis dengan menggunakan kaidah Business Process Modeling and Notation (BPMN) dengan bantuan software Bizagi Modeller. Digunakan pendekatan Business Process Management (BPM) dalam memodelkan proses bisnis untuk membantu meningkatkan efisiensi dan efektivitas bisnis. Dari hasil pengerjaan didapatkan proses bisnis yang telah dimodelkan sebanyak 69 proses bisnis, terbagi atas 55 proses pada proses Peningkatan Kualitas Pendidikan dan 14 proses pada proses Peningkatan Kenyamanan, Keamanan Dan Ketertiban Lingkungan.Kata kunci: Dinas Pendidikan dan Kebudayaan, Proses Bisnis, Standar Operating Prosedure, Business Process Modeling and Notation, Business Process Management